Experimental study on the exposure level of surgical staff to SARS-CoV-2 in operating rooms with mixing ventilation under negative pressure. (1st June 2022) - Bi, Yang; Aganovic, Amar; Mathisen, Hans Martin; Cao, Guangyu
Abstract: The purpose of this study was to reveal the exposure level of surgical staff to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) from the patient's nose and wound during operations on COVID-19 patients. The tracer gas N2 O is used to simulate SARS-CoV-2 from the patient's nose and wound. In this study, concentration levels of tracer gas were measured in the breathing zones of these surgical staff in the operating room under three pressure difference conditions: −5 pa–15 pa and −25 pa compared to the adjunction room. These influencing factors on exposure level are analyzed in terms of ventilation efficiency and the thermal plume distribution characteristics of the patient. The results show that the assistant surgeon faces 4 to 12 times higher levels of exposure to SARS-CoV-2 than other surgical staff. Increasing the pressure difference between the OR lab and adjunction room can reduce the level of exposure for the main surgeon and assistant surgeon. Turning on the cooling fan of the endoscope imager may result in a higher exposure level for the assistant surgeon. Surgical nurses outside of the surgical microenvironment are exposed to similar contaminant concentration levels in the breathing zone as in the exhaust. However, the ventilation efficiency is not constant near the surgical patient or in the rest of the room and will vary with a change in pressure difference. This may suggest that the air may not be fully mixed in the surgical microenvironment. Highlights: Tracer gas is used to simulate SARS-CoV-2 in the operating room. The distribution features of SARS-CoV-2 in NPOR are summarized. The assistant surgeon faces 4 to 12 times higher levels of exposure to SARS-CoV-2. Endoscopic cooling fans may increase the exposure level of assistant surgeons. Increasing the pressure difference may lower the exposure risk to SARS-CoV-2.